Peran Permainan Congklak dalam Mengembangkan Kemampuan Kognitif Anak Usia Dini - Fauzia Polamolo; Nurulaeni Laide; Salsiyo Lamatupu; Nindi Astuti (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
Traditional games play a strategic role as learning media that can support the cognitive development of early childhood. This article comprehensively discusses how congklak can significantly contribute to improving children's thinking skills. Based on an analysis of cognitive development theory and the characteristics of congklak, this activity not only provides a fun playing experience but also develops various important skills, such as counting, strategy, patience, concentration, and analytical thinking. Furthermore, the interactions that occur during congklak games help improve children's social skills, cooperation, sportsmanship, and emotional control, all of which are closely related to the development of cognitive function. With the support and active involvement of parents and educators, congklak can be utilized as an effective, engaging, and easily applicable learning method in various non-formal and formal educational contexts. Therefore, congklak games are suitable as part of educational activities aimed at promoting optimal cognitive growth and development in children from an early age, while simultaneously preserving local cultural values.